O processo constitutivo da Resolução de Problemas como uma temática da pesquisa em Educação Matemática: um inventário a partir de documentos dos ICMEs - Morais, Rosilda dos Santos Morais [UNESP] (2015)
The following research was interested in investigating Problem Solving as a subject of research in mathematics education from a historiographical standpoint. For our research the strategy adopted was to analyze documents (understood in the research to be CDs and books: proceedings, short communications and poster summaries of selected lectures, final programs and additional publications) produced in eleven events of the International Congress on Mathematical Education (ICME), from 1969 (ICME-I) to 2008 (ICME-XI), by surveys where the theme was Problem Solving understood as a Methodological. Once the research strategy was clear, the theoretical framework adopted considered the ways to make history according to perspectives that, today, mold the research in the History of Mathematics Education. The presentation of this production was given through an inventory which, coupled with the inbuilt theory, enabled us to respond to the questions first raised, and the main question of the research, which was interested in checking out how the process of including Problem Solving as a thematic research in Mathematics Education, from the documents produced in the ICMEs, was done. From the research undertaken it was possible to identify movements of Problem Solving so that it made sense to conceive of it as a theory that is always in the process of being set up and never made. This movement was outlined in a periodization of Problem Solving, internationally read through the ICME, distributed in four phases: Phase 1 - it was not the subject of discussion at ICME-I; Phase 2 - Problem Solving immerses in the ICME-II; Phase 3 - comprising the ICME-III (1976, Karlsruhe), ICME-IV (1976, Berkeley) and ICME-V (1980, Adelaide;) expresses a nature of Problem Solving in the following features: incipient in relation to research classroom; of continuity in theoretical or practical aspects; of dissolution in other areas, with the approach of this theme to ...